Eksekusi Terhadap Putusan Hakim Yang Telah Berkekuatan Hukum Tetap Dalam Perkara Faraid di Mahkamah Syar’iyah Jantho - Muhammad Syukri; Azhari Yahya; Iman Jauhari (Syiah Kuala Law Journal, 2018)
Pasal 54 ayat (2) Undang-Undang Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman menjelaskan bahwa: “Pelaksanaan putusan pengadilan dalam perkara perdata dilakukan oleh panitera dan juru sita dipimpin oleh Ketua Pengadilan.” Namun pada kenyataannya ada para pihak yang menolak melaksanakan kewajibannya sebagaimana termuat dalam putusan pengadilan meskipun putusan tersebut telah berkekuatan hukum tetap (in kracht van gewijsde). Penelitian ini bertujuan untuk menganalisis putusan hakim dalam perkara faraid di Mahkamah Syar’iyah Jantho sehingga tidak dapat dieksekusi, hambatan dalam melakukan eksekusi dan upaya yang dilakukan untuk mencegah hambatan pelaksanaan eksekusi tersebut. Metode Penelitian ini adalah yuridis empiris melalui pengambilan data lapangan dan kepustakaan. Penelitian lapangan dimaksudkan untuk memperoleh data primer. Penelitian kepustakaan sebagai data sekunder dilakukan dengan cara mempelajari buku-buku, peraturan perundang-undangan dan literatur yang ada relevansi dengan masalah yang diteliti. Hasil penelitian menunjukkan bahwa pertimbangan Hakim hanya mengikuti prosedur penegakan hukum formil dan materil sebagaimana diatur dalam peraturan perundang-undangan yang berlaku. Majelis Hakim kurang menggali hukum nilai-nilai hukum adat yang berlaku dalam masyarakat. Hambatan dalam melakukan eksekusi karena pihak tergugat memanfaatkan celah hukum mengajukan gugatan ke Pengadilan Negeri. Upaya yang dilakukan untuk mencegah hambatan tersebut dengan memberikan pemahaman hukum kepada masyarakat melalui meja informasi tentang proses hukum dalam perkara perdata.According Article 54 section (2) of Law Number 48 of 2009 of Judiciary Power (Law of Judiciary Power) states that: “The Implementation of court judgment in civil case is conducted by secretary of court and bailiff led by Head of the Court”. However, in fact, there are several parties refuse to perform the obligation according to the court judgment, even when it is conducted by the secretary of court and the bailiff and led by the Head of the Court. The practice of the court judgment faces several obstacles instead of being in permanent legal force status (in kracht van gewijsde). This research is conducted to analyze the legal consideration of in faraid case at Sharia Court of Jantho which makes it non-executable, the obstacles in performing execution towards the court judgment of permanent legal force at Sharia Court of Jantho, and the efforts implemented to prevent occurring obstacles in executing the court judgment at Sharia Court of Jantho. The research method used in this study is empirical yuridicial through data gained in field and library research. Field research is performed to collect primary data by doing interview to respondents and informants. The library research is conducted by studying books, laws and other relevant literatures. The results of this study shows that the legal consideration of in faraid case at Sharia Court of Jantho is in accordance to the procedure of law enforcement which refers to formil and materiil law as stated in Law of Judiciary Power. The obstacle in doing the execution towards the court judgment of permanent legal force at Sharia Court of Jantho in the form of verdict without the presence of the defendant (verstek), legal review, and the lack of understanding of the disputing parties that new supplication or request to the Head of the Sharia Court is needed to do the execution. The efforts that is done to overcome the obstacle is by giving the knowledge and understanding of law to public via information desk concerning the court process and technical phases of civil case and the expenses that occurs.